Features and Constitutive Model of Gypsum’s Uniaxial Creep Damage considering Acidization - Wei Chen; Wen Wan; Senlin Xie; Wenlong Kuang; Wenqing Peng; Qiuhong Wu; Shasha Tong; Xianqing Wang; Xiaoyu Tang (Geofluids)
Acidic fluids cause rock erosion and further endanger the safety of rock engineering, especially the corrosion of pillars by acidic or weakly acidic groundwater. In this paper, the rock samples in the gypsum mining area were taken as the research object. Uniaxial compression creep tests were carried out under neutral water, pH=6 and pH=5 hydrochloric acid solutions, respectively. Meanwhile, the specimens before and after saturation were observed by an electron microscope scanner. The results show that (1) the gypsum specimens with pH=5 hydrochloric acid were damaged at the first stress level, while that with pH=6 and pH=7 were destroyed at the second stress level. The failure modes of the three groups were basically the same, with cleavage and end damage of different degrees. The difference is that the failure time of the former is earlier than that of the latter, which indicates that the stronger acidity causes greater corrosion on the creep of the samples. (2) From the perspective of microstructure, the samples saturated in the neutral aqueous solution and dry state are compact and complete in structure, and the whole is relatively homogeneous. However, after saturating in the acid solution, the samples significantly increased dense pores with large size and loose structure. Due to the rapid increase, the surfaces of the samples are almost like “holes”. (3) A new nonlinear creep constitutive model was established by connecting Burgers model with nonlinear viscoplastic body (NVPB) model in series, which can well describe the creep characteristics of gypsum rocks under acid corrosion.